2022
DOI: 10.12688/f1000research.75869.2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the safety and immunogenicity profile of an azoximer bromide polymer-adjuvanted subunit influenza vaccine.

Abstract: A systematic review of clinical trials conducted with a low-dose inactivated influenza vaccine adjuvanted by azoximer bromide (AZB, Polyoxidonium), was performed to compare vaccine reactogenicity against non-adjuvant vaccines. We also assessed whether lower amounts of antigen per viral strain in AZB-adjuvanted vaccines affected antibody responses. A robust search strategy identified scientific publications reporting 30 clinical trials, comprising data on 11,736 participants and 86 trial arms, for inclusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…In 2022 there was an analysis conducted of the safety and immunogenicity profile of an azoximer bromide polymer-adjuvanted subunit influenza vaccine, which included trials performed between 1993 and 2016 and comprised 11,736 participants aged between 6 months and 99 years [55]. It showed that Grippol family vaccines induced antibody production in both children and adults up to 60 years at levels similar to vaccines with the standard amount of HA.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022 there was an analysis conducted of the safety and immunogenicity profile of an azoximer bromide polymer-adjuvanted subunit influenza vaccine, which included trials performed between 1993 and 2016 and comprised 11,736 participants aged between 6 months and 99 years [55]. It showed that Grippol family vaccines induced antibody production in both children and adults up to 60 years at levels similar to vaccines with the standard amount of HA.…”
Section: Discussionmentioning
confidence: 99%
“…(Vaccines, Frontiers Immunology, Austin Journal of Vaccines & Immunotherapeutics, Intechopen и др. )[16,17,18,19]. По результатам исследования тривалентную инактивированную субъединичную адъювантную вакцину можно рекомендовать, как препарат выбора в рутинной практике иммунизации в Республике Казахстан, поскольку включенный в состав адъювант (МНН: азоксимера бромид) обладает антиинфекционной, противоопухолевой и детоксицирующей активностью [26].…”
unclassified